Government size and output volatility : should we forsake automatik stabilization - Debrum, Xavier; Pisani-Ferry, Jean.; Sapir, Andre; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2008)
Prior to the launch of the euro, academics and policymakers were concerned that the loss of the monetary policy instrument would deprive participating countries of a vital tool to respond to country-specific economic shocks. This concern was rooted in the generally accepted proposition that market-based adjustment channels-i.e. labour mobility and capital flows-tended to be weaker among euro area countries than among regions of existing monetary unions such as the United States. Automatic stabilizers had long been regarded as playing a key role in macroeconomic stabilization. In particular, they were generally considered as having contributed significantly to the decrease of output volatility witnessed in Europe and in the United States after World War II, when the size of governments increased substantially on both sides of the Atlantic. Hence it was hoped that improved national fiscal policy could partly make up for the loss of monetary policy in stabilizing national macroeconomic conditions. The aim of the paper is to discuss this issue in the light of recent experience.
Economic Papers